Demographics and the Housing Market : Japan's Disappearing Cities - Hashimoto, Yuko (IMF Working Papers; Working Paper, 2020)
How does a shrinking population affect the housing market? In this study, drawing on Japan's experience, we find that there exists an asymmetric relationship between housing prices and population change. Due to the durability of housing structures, the decline in housing prices associated with population losses is estimated to be larger than the rise in prices associated with population increases. Given that population losses have been and are projected to be more acute in rural areas than urban areas in Japan, the on-going demographic transition in Japan could worsen regional disparities, as falling house prices in rural areas could intensify population outflows. Policy measures to promote more even population growth across regions, and avoid the over-supply of houses, are critical to stabilize house prices with a shrinking population.